Evaluation of the Effectiveness of the Use of Digitalization Systems in the Implementation of e-Government in Indonesia (Case Study in Data Integration and Exchange Management Applications-MANTRA) - Siswanto Muhartono, Djoko; Nur Laili, Alivia Novita (Institut Riset dan Pengembangan Indonesia, 2025)
This article examines the evaluation of the effectiveness of the digitalization system in the implementation of e-government in Indonesia with a case study on the MANTRA Application developed by the Ministry of Communication and Information Technology (Kemkominfo). The development of this application began in 2011. The beginning of the concept of E-Government in Indonesia was formed through public policy in the form of Presidential Instruction Number 6 of 2001 which described government support in the use of information and communication technology (ICT) to improve the quality of public services in the digital system. Based on data from the Central Statistics Agency (BPS), it shows that in 2022, 66.48% of the Indonesian population has accessed the internet. However, data on internet users will increase in 2024. This can be seen through a survey by the Indonesian Internet Service Providers Association (APJII) that the level of internet users in Indonesia will reach 79.5% in early 2024. The data collection techniques used in this study are by means of documentation, interviews, and observations in data collection through documents related to the use of digital systems in the implementation of e-government. The findings of this research will be presented based on the analysis of data obtained that the application of applications with technological advances in the current era is considered more effective and efficient in assisting the bureaucracy in solving community problems and supporting the development of public services as a link in achieving common goals.